GPI-anchored glycoproteins - Ferguson, Michael (Henry Stewart Talks, 2012)
What are GPI membrane anchors and examples of their occurrence, The biosynthesis of GPI anchors, The structure of GPI anchors and analytical methods, Inhibitors of GPI biosynthesis as therapeutic agents, Biological functions of GPI membrane anchors